Fishing Industry Perspectives on the Development of Offshore Wind - Beitl, Christine; Hiltonsmith, Julia (Maine Policy Review, 2023)
The Maine Legislature recently passed LD 1895 to advance the development of offshore wind to meet the state’s clean energy targets. This article explores general concerns among commercial fishermen about the potential impacts of offshore wind and identifies some of the mechanisms in place to support Maine’s fisheries during this time of critical technological change. First, we trace the history and provide a brief overview of policy and action around offshore wind in Maine. Then we present fishing industry perspectives heard at public hearings and events that were organized to proactively reduce conflicts in marine spatial planning through stakeholder engagement. Fishing industry members raised thoughtful concerns about equity, expediency of planning, the industrialization of the ocean, and ecological impacts of leasing in a dynamic socio-environmental system.